Case Report: A case of recurrent thrombosis in pediatric antiphospholipid syndrome associated with pediatric onset systemic lupus - Liu, Lingjuan; Liu, Liqun; Zhang, Lu; Huang, Peng; Dang, Xiqiang; Shuai, Lanjun; Li, Xingfang; Li, Yongzhen; Mao, Dingan; Wu, Xiaochuan; Cao, Yan (Frontiers in Pediatrics, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease with multi-system involvement as the main manifestation, and has complex and diverse clinical features. Studies on large samples have revealed that SLE patients have a significantly increased risk of thrombotic events, which are also one of the important causes of morbidity and mortality in SLE patients. Antiphospholipid syndrome (APS) is a rare autoimmune disorder characterized by recurrent arterial and venous thrombosis, pregnancy-related complications, and the persistence of antiphospholipid antibodies at a 12-week interval. There are few reports about SLE coexisting with APS in children. This paper reported a school-age patient who started the disease with gross hematuria after bumping into the waist. The initial diagnosis of renal contusion was then confirmed by color Doppler ultrasound as renal vein and inferior vena cava embolism. She suddenly developed severe chest pain and dyspnea 3 days after hospitalization. And imaging supported pulmonary embolism with massive proteinuria, hypoalbuminemia, and hypercholesterolemia. The initial diagnosis was nephrotic syndrome (NS) with arteriovenous embolization, and popliteal vein embolism occurred again 5 years later, and she was thus diagnosed with SLE coexisting with APS. Afterwards, we discussed the possible mechanism and therapeutic strategies of SLE&APS that started with nephrotic syndrome, in order to achieve early identification and treatment of the disease and improve the prognosis of children.